Reports of Avian Influenza H5N1 in Cats and Dogs - Burgos, Sigfrido; Burgos, Sergio A. (International Journal of Poultry Science, 2007)
Avian Influenza virus (H5N1 subtype) interspecies transmission capability is a characteristic feature that has attracted worldwide attention as a potential risk to human health. Pet carnivores (cats and dogs) are susceptible to infection, shed virus, can remain asymptomatic and thus can be silent disease carriers. These potential intermediate hosts are commonly kept as pets in rural and urban households and therefore could serve as vehicles for viral disease spread to children and adults.